Lactation physiokinetics—using advances in technology for a fresh perspective on human milk transfer - Francis, Jimi; Flynn, Paul; Naowar, Maisha; Indic, Premananda; Dickton, Darby (Frontiers in Pediatrics, 2023)
Though the nature of breastfeeding is critical, scant information is available on how the action of the milk transfer from mother to infant is regulated in humans, where the potential points of dysfunction are, and what more can be done to optimize breastfeeding outcomes. Imagine, if we fully understood the bio-mechanical process of milk ejection at a cellular level, how we might be able to assist the infant's struggle with fast or slow milk ejection or if we better understood how breast milk supply is bio-physiologically dictated by the removal of milk or environmental changes how we might address early milk loss or engorgement. While better therapeutic strategies are needed, before they can be devised, a basic scientific understanding of the biomechanical mechanisms that regulate human milk transfer from breast to stomach must first be identified, defined, and understood.While Systems Biology has been suggested as a method for understanding human milk, SystemsMedicine has yet to be used to understand the complexity of breastfeeding. Combining systems biology and systems medicine into a conceptual framework with engineering design principles can bring new perspectives to the system of human milk transfer. This exploratory study uses this framework to characterize Maternal/Infant Lactation physioKinetics (MILK) utilizing a Biosensor ARray (BAR) as a data collection method. We explored human milk regulatory factors to understand points of regulation and potential points of dysregulation.